EVALUASI TERHADAP PELAKSANAAN ADMINISTRASI KESISWAAN PADA SEKOLAH MENENGAH PERTAMA NEGERI 1 KUSAN HILIR KABUPATEN TANAH BUMBU - Ade Hermawan (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2019)
The implementation of Student Administration at Kusan Hilir 1 Junior High School includes student planning activities, admission of new students, recording of students in the master book, administration of student attendance, school discipline, student transfer, student organization activities, and administration of graduation and alumni. All student administration activities have been done well by the administration staff of the Kusan Hilir 1 Junior High School. Factors Influencing the Implementation of Student Administration at the 1 Kusan Hilir State Middle School are education of administrative staff and the availability of facilities and infrastructure owned by Kusan Hilir 1 Junior High School.